High serum estradiol confers no risk for breast cancer: another disparity for sub Saharan Africa women - (:unkn) unknown (Pan African Medical Journal, 2012)
There are breast cancer epidemiological and tumor behaviour disparities between black women in sub Saharan Africa and their counter parts in western high resource countries. In Uganda, the incidence of breast cancer has nearly tripled in over a four decades for uncertain reasons. High serum estradiol is a known risk factor for breast cancer among women in high resourced nations. The objective of this study was to establish whether high serum estradiol is an associated risk for breast cancer amongst a group of black Ugandan women. Methods: A case control study, conducted over eight month period with incident breast cancer as cases and the controls were without breast cancer but at risk and representative of the population from which the cases were chosen. Questionnaires were administered, clinical examination was done, serum estradiol level estimation was done using cobase immunoassay analyzer using Electro chemiluminescence Immuno assay (ECLIA). Data was analyzed using logistic regression model, and a p - value of less than 0.05 was considered significant. IRB approval was secured. Results: A total of 140 women participated, 70 cases and 70 controls. The median estrogen levels was 43.2 pg/ml with IQR of 18.48 to 75.8 pg/ml, the value was higher among premenopausal women than those without cancer but with no statistical significance. No association was found between level of estradiol and breast cancer (p 0.647). The median oestrogen levels were significantly higher than normal levels in Caucasian women. Conclusion: There was no association between level of estradiol and breast cancer. This is yet another disparity between women of African origin and the non Africans in high resourced countries. There is need to explore more to explain this disparity.
Keywords: serum estradiol; breast cancer; sub Saharan Africa women